The HAC1 histone acetyltransferase promotes leaf senescence and regulates the expression of ERF022. (27th August 2019) - Hinckley, Will E.; Keymanesh, Keykhosrow; Cordova, Jaime A.; Brusslan, Judy A.
Abstract: Nutrient remobilization during leaf senescence nourishes the growing plant. Understanding the regulation of this process is essential for reducing our dependence on nitrogen fertilizers and increasing agricultural sustainability. Our laboratory is interested in chromatin changes that accompany the transition to leaf senescence. Previously, darker green leaves were reported for Arabidopsis thaliana hac1 mutants, defective in a gene encoding a histone acetyltransferase in the CREB‐binding protein family. Here, we show that two Arabidopsis hac1 alleles display delayed age‐related developmental senescence, but have normal dark‐induced senescence. Using a combination of ChIP‐seq for H3K9ac and RNA‐seq for gene expression, we identified 43 potential HAC1 targets during age‐related developmental senescence. Genetic analysis demonstrated that one of these potential targets, ERF022, is a positive regulator of leaf senescence. ERF022 is regulated additively by HAC1 and MED25, suggesting MED25 may recruit HAC1 to the ERF022 promoter to increase its expression in older leaves.